2016
DOI: 10.2109/jcersj2.15203
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum covering 3&ndash;10 &micro;m using a As<sub>2</sub>Se<sub>3</sub> core and As<sub>2</sub>S<sub>5</sub> cladding step-index chalcogenide fiber

Abstract: A high numerical aperture (NA) step-index fiber with As 2 Se 3 core and As 2 S 5 cladding was fabricated for deep mid-infrared (MIR) transmission over 10¯m. MIR supercontinuum generation covering the wavelength from 3 to 10¯m was successfully demonstrated in this fiber using a MIR pulsed laser source with¯J-level energy output around 7¯m. A 4-cm-long fiber sample is sufficient to enable a spectral broadening spreading from 3 to 10¯m in a 20 dB dynamic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As one of the promising applications of chalcogenide fibers, Mid-IR supercontinuum generation has been investigated extensively with both step-index and microstructured chalcogenide fibers [41][42][43][44].…”
Section: Supercontinuum Generation In Chalcogenide Mofsmentioning
confidence: 99%
“…As one of the promising applications of chalcogenide fibers, Mid-IR supercontinuum generation has been investigated extensively with both step-index and microstructured chalcogenide fibers [41][42][43][44].…”
Section: Supercontinuum Generation In Chalcogenide Mofsmentioning
confidence: 99%
“…At present, supercontinuum light and a frequency comb are attractive light sources. (7)(8)(9) Poly(dimethylsiloxane) is used for integrating the microchannel and embedding the fibers; however the simple setting means low alignment accuracy and limited illumination efficiency. (10) Many cells are heavier than water.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on SC generation in an optical fiber have been carried out to cover the spectral range from ultraviolet to MIR. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Many researchers have demonstrated SC generation in a silica fiber. [5][6][7] However, the intrinsic transmission window of fused silica limits SC extension above 3 µm.…”
mentioning
confidence: 99%
“…10) So far, many researchers have demonstrated MIR SC generation in Ch-SIFs. 11,[14][15][16][17][18] In 2016, Cheng et al demonstrated MIR SC extending from 2.0 to 15.1 µm in a Ch-SIF. 18) In most of the studies, broadband SC has been generated by pumping in the anomalous dispersion (AD) regime near the zero-dispersion wavelength (ZDW).…”
mentioning
confidence: 99%